Farmers Direct Coffee asks WUR to make a dedicated derivative of ACE calculator in order to make climate impact of their chain transparent to customers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Based on webinars of ACE calculator and direct contact the company recognizes that the ACE functionality matches their interest in transparency on climate impact, and meanwhile can serve to proof the sustainability distinguishment compared to competitor.